Hizbut Tahrir Sebagai Gerakan Sosial (Melihat Konsep HT mengenai Negara) - Khusnul Khotimah (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
This research is aimed to discuss the history and development of HT in Indonesia, the understanding on the HT’s concept of state, and kind of challenges of the HT movement. Using Piötr Stzompka’s theory of social movement, it seems that HT used  social movement by keeping on doing critics and showing the inadequacy of system of government, at the same time it offers khilafah Islamiyah concept as the alternative. The research uses a qualitative phenomenological method through the method of data collection found in books, articles and interviews in magazines and websites. The article uses the interpretative type of data analysis. The study shows that HT is one of Islamic movements preserving a conservative ideology. The main agenda is bringing back Islam authority in the past and developing Islamic state led by a Khalifah through bai’at. The model of leadership in this ‘dream state’ is a sole leadership, while Islamic state is geographically an unlimited state. In other word, the khalifah is the leader of Islamic state for all around the world. This community has spread the ideology in many regions and has reached circles in different kinds of background and society. The purpose is to promote khilafah Islamiyah in the world. HT tends to reject secularism because they classify this concept as kufur that against the Islamic view.  From the beginning, HT has a clear and unchanged attitude to this case. This can be seen from its consistency using books from HT’s Amir that also be used in Indonesia.